2010
DOI: 10.1007/s00586-010-1339-4
|View full text |Cite
|
Sign up to set email alerts
|

Nucleus pulposus deformation in response to lumbar spine lateral flexion: an in vivo MRI investigation

Abstract: Whilst there are numerous studies examining aspects of sagittal plane motion in the lumbar spine, few consider coronal plane range of motion and there are no in vivo reports of nucleus pulposus (NP) displacement in lateral flexion. This study quantified in vivo NP deformation in response to side flexion in healthy volunteers. Concomitant lateral flexion and axial rotation range were also examined to evaluate the direction and extent of NP deformation. Axial T2-and coronal T1-weighted magnetic resonance images … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 22 publications
2
8
0
Order By: Relevance
“…The results of the present study offer three points for consideration. First, these findings support a finding by Fazey et al 2 that there is no significant correlation between the degree of lateral flexion and the magnitude of the disc hydration shift. Second, the results indicate that the maneuver of SG produces a comparable mechanical influence to lumbar discs, Table 3 The mean (SD) segmental rotation angles (degrees) at end-range side bending (SB) and side gliding (SG) positions to the left and effect sizes (Hedges's g) of the difference between the two positions.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The results of the present study offer three points for consideration. First, these findings support a finding by Fazey et al 2 that there is no significant correlation between the degree of lateral flexion and the magnitude of the disc hydration shift. Second, the results indicate that the maneuver of SG produces a comparable mechanical influence to lumbar discs, Table 3 The mean (SD) segmental rotation angles (degrees) at end-range side bending (SB) and side gliding (SG) positions to the left and effect sizes (Hedges's g) of the difference between the two positions.…”
Section: Discussionsupporting
confidence: 88%
“…[1][2][3][4][5][6] Disc hydration normally shifts to the contralateral side of the movement plane. 2,4 The directional response of the disc to various loading strategies has been used as the theoretical explanation for a directional preference in the Mechanical Diagnosis and Therapy (MDT) system. In that system, side gliding (SG) is used as a repeated movement, or static loading, strategy for assessment, and treatment of patients who need lateral loading strategies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings make L-4 the vertex of the angle formed in the lumbar spine during lateral flexion. 8 These biomechanical results can be correlated to the findings of our study. Lumbar nerve roots originating above the L-4 vertebral body (L-1 to L-3) are exposed to higher levels of stretch in a laterally flexed position.…”
Section: Discussionsupporting
confidence: 85%
“…2 It has been shown that asymmetrical loading of the disc leads to displacement of the nucleus pulposus (NP) to areas of least pressure. 3 Furthermore, it has been suggested that radial fissures bring about excessive mechanical strain on surviving annular layers, and that displaced fragments could mechanically stress surviving and innervated outer annular layers causing pain. 4 Mechanical diagnosis and therapy (MDT) proposed by McKenzie is a comprehensive management strategy for a range of spinal pain disorders using specific forms of exercise individually prescribed.…”
mentioning
confidence: 99%